COPING AND ACCEPTANCE PAIN WITH QUALITY OF LIFE ADOLESCENTS WITH PRIMARY DYSMENORRHEA - Tien Aulia Rahmawati; Nur Ainy Fardana; Jimmy Yanuar Annas (Universitas Airlangga, 2021)
Background: Dysmenorrhea is a symptom of pain experienced before or during menstruation. Based on literature review and previous research, the negative impact of basic education on adolescent girls has decreased quality of life by 80%. Good quality of life after experiencing primary dysmenorrhea with coping strategies and pain acceptance. This study aims to analyze the relationship between coping and acceptance with quality of life in adolescents with primary dysmenorrhea. Methods: This study uses analytical observational with a cross sectional approach. A sample of 43 students was obtained using simple random sampling at SMP PGRI Mekarmanik with the inclusion criteria of adolescent girls aged 13-16 years who had experienced menstruation in the last 3 months and experienced primary dysmenorrhea. Data collection was carried out online using a Google Form containing structured questionnaires WOC, CPAQ-8, WHO-QOLBRIEF and NPRS. Then analyze the data with Chi Square and Rank Spearman tests with a significance limit of 5%. Results: The percentage of respondents who experienced primary dysmenorrhea was 100% with the majority of moderate pain degrees 51.16%. There is no relationship between coping strategies and quality of life (p=0.897) because the majority of respondents use the EFC coping strategy, namely Emotional Focused Coping, where this strategy is used by people who are chronic and have low quality of life. There is a relationship between pain acceptance and quality of life (p = 0.006), it is found that high pain acceptance makes individuals adapt and reduce their attention to pain so as to optimize their daily functioning. Conclusion: There is no significant relationship between coping strategies and quality of life, but there is a significant relationship between pain acceptance and quality of life.